Nghiên cứu chế tạo màng trên cơ sở tinh bột/PVA cho phân NPK nhả chậm - Khoa, Nguyễn Cửu; Bé Thi, Dương Thị; Quyển, Trần Ngọc; Phương, Lê Thị (Vietnam Journal of Chemistry, 2015)
Membranes coating for controlled release fertilizer (CRF) were prepared from poly(vinylalcohol)/starch using formaldehyde as a crosslinker. The influence of the blending ratio of starch/PVA and the content of formaldehyde on the swell of the film has been investigated. The membrane structure was observed by FT-IR and NMR. The results showed that the obtained membrane was high durability and economic effect at the weight ratio of starch: PVA:aldehyde = 9:1:0.6. After 15 days, the release behavior of nitrogen, phosphate and potassium was 41.67 %, 46.04 %, 43.63 %, respectively. The encapsulated system exhibiting a good controlled-release fertilizer and water-retention capacity, biodegradation and environment friendly, could be especially useful in agricultural and horticultural applications.